Ensemble modeling of long-term radiation belt dynamics: accounting for variability in radial diffusion - Lee, Sang-Yun; Tu, Weichao; Cunningham, Gregory S.; Cowee, Misa M. (Frontiers in Astronomy and Space Sciences, 2026)
This study presents ensemble modeling of outer radiation belt dynamics observed by Van Allen Probes throughout 2017 using DREAM3D simulations. We utilize a recently developed empirical radial diffusion coefficient (DLL) model with statistical distributions, employing two outer boundary (OB) conditions: Van Allen Probes data at L*=5.5 and GOES data at L*=6, for two magnetic moments μ=512 keV/G and μ=1237 keV/G. The results demonstrate that OB location critically influences model performance. A model using Van Allen Probes OB at L*=5.5 better reproduces observations, particularly for high μ electrons. In this scenario, radial diffusion alone can largely explain the dynamics because the OB is located near the phase space density (PSD) peak region. Stronger DLL outside the plasmasphere effectively captures inward/outward radial diffusion to/from the OB, while an intermediate DLL around the 30th percentile best matches electron PSD inside the plasmasphere. With GOES OB at L*=6, not only does strong DLL remain crucial for achieving good performance, but chorus heating also becomes critical. Model performance inside the plasmasphere is the best for the intermediate DLL but consistently worse than that outside the plasmasphere, suggesting a need for improved DLL and loss inputs in the plasmasphere.